Pengaruh Kompensasi, Disiplin Kerja dan Motivasi terhadap Kinerja Karyawan (Studi Kasus Pada Pekerja UD Rahma Jaya Temanggung): The Influence of Compensation, Work Discipline, and Motivation on Employee Performance (Case Study at UD. Rahma Jaya Temanggung) - Dewi, Rinda Ardina; Subiyanto, Didik; Herawati, Jajuk (Efektor, 2023)
Employees at UD Rahma Jaya Temanggung were examined to see if there is a relationship between compensation, work discipline, and motivation. For this investigation, we turn to SPSS 25 and its ability to quantitatively analyze data. Researchers from UD Rahma Jaya Temanggung collected information using a media questionnaire that can be accessed via the Google Forms website. Overall, 195 participants were included in the analysis. Samples were taken using the slovin formula as many as 66 people at UD Rahma Jaya Temanggung workers, and the sampling method was simple random sampling. To support the hypothesis, data analysis was performed using statistical methods which included survey validity and reliability tests, multiple linear regression, and significance tests such as t-test and f-test. The results of the experiments in this study reveal that compensation, work discipline, and motivation have a large impact on productivity. In addition, at UD Rahma Jaya Temanggung work discipline and motivation both have a partial and quite large effect on employee performance, while compensation has a partial negative effect and is not significant.